2017
DOI: 10.1097/njh.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Family-Centered Care in the Pediatric Intensive Care Unit

Abstract: This paper reports result from a systematic search and thematic analysis of qualitative literature to identify key issues related to family-centered care, behaviors, and communication skills that support the parental role and improve patient and family outcomes in the PICU. Five themes were identified: 1) sharing information; 2) hearing parental voices; 3) making decisions for or with parents; 4) negotiating roles; and 5) individualizing communication. These themes highlight several gaps between how parents wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 65 publications
1
46
0
4
Order By: Relevance
“…Studies have shown that family-centered care results in positive outcomes and experiences for hospitalized children and their families, improves satisfaction among health professionals, and reduces medical costs [6]. Several studies have been conducted of pediatric nurses in various nations, examining their attitudes and perceptions towards family-centered care in pediatric wards [3,[7][8][9], pediatric intensive care units [10], and pediatric cancer units [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that family-centered care results in positive outcomes and experiences for hospitalized children and their families, improves satisfaction among health professionals, and reduces medical costs [6]. Several studies have been conducted of pediatric nurses in various nations, examining their attitudes and perceptions towards family-centered care in pediatric wards [3,[7][8][9], pediatric intensive care units [10], and pediatric cancer units [11].…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children admitted to neonatal intensive care unit (NICU) and pediatric intensive care unit (PICU) seek information to support participation in their child's care and treatment decisions to give their child the best possible outcome. [1][2][3][4][5][6][7] Parents experience stress when they encounter barriers to their involvement, such as receiving incomplete or conflicting information, or when their expertise about their child is not incorporated into the treatment plan. [6][7][8][9][10] Additionally, parents often report feelings of uncertainty and fear about their child's outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual practices played a pivotal role in promoting faith by creating the means and beliefs by which to have such faith, which was central and essential for these parents to deal with their child's illness and to continue their lives with value and meaning. Healthcare providers should be aware of parental stressors during decision-making, identifying parental needs as both care providers and care recipients, in order to minimize their stress, preserve their wellbeing, and provide family-centred care (Richards et al, 2017;Shudy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%